Persistent coccydynia – the importance of a differential diagnosis. (29th July 2011) - Blocker, Oliver; Hill, Susan; Woodacre, Timothy
Abstract : The authors present the case of a sacral chordoma in which the diagnosis was delayed as the patient was diagnosed and treated as coccydynia. Persistent, severe coccydynia following minor trauma is common1 but the symptom can also be caused by significant underlying disease. The correct diagnosis was made in this patient but after significant delay. The presentation of this case involved multiple specialties and provides several learning points regarding the importance of thorough history taking and clinical examination. It highlights the importance of 'red flag' symptoms of low back pain2 which need to be fully investigated.